Acetazolamide: Old drug, new evidence?. Issue 3 (14th June 2022) - Shukralla, Arif Ali; Dolan, Emma; Delanty, Norman
Abstract: Acetazolamide is an old drug used as an antiepileptic agent, amongst other indications. The drug is seldom used, primarily due to perceived poor efficacy and adverse events. Acetazolamide acts as a noncompetitive inhibitor of carbonic anhydrase, of which there are several subtypes in humans. Acetazolamide causes an acidification of the intracellular and extracellular environments activating acid‐sensing ion channels, and these may account for the anti‐seizure effects of acetazolamide. Other potential mechanisms are modulation of neuroinflammation and attenuation of high‐frequency oscillations. The overall effect increases the seizure threshold in critical structures such as the hippocampus. The evidence for its clinical efficacy was from 12 observational studies of 941 patients. The 50% responder rate was 49%, 20% of patients were rendered seizure‐free, and 30% were noted to have had at least one adverse event. We conclude that the evidence from several observational studies may overestimate efficacy because they lack a comparator; hence, this drug would need further randomized placebo‐controlled trials to assess effectiveness and harm.